Turbulent heat transfer enhancement in round tubes by inserting triple twisted-tapes - Eiamsaard, S.; Promthaisong, P.; Chuwattanakul, V. (My University, 2015)
Turbulent flow characteristics and heat transfer performances in a round tube equipped with triple twisted tapes are investigated numerically. Effects of the triple twisted tapes at different twist ratios on the heat transfer and thermal performance characteristics are reported. The results of velocity and temperature fields, and the local heat transfer coefficients as well as the flow structure in tube with tape inserts are also given. A round tube wall is subjected to a constant wall temperature condition. Thermal field, heat transfer and fluid flow characteristics are studied using computational fluid dynamics (CFD) analysis. Computations, based on a finite volume method, are carried out by utilizing the Renormalized Group (RNG) k-e turbulence model. The investigation is carried out for triple twisted tapes with y/W = 2.0, 3.0 and 4.0 in round tubes for laminar air flow with Reynolds numbers between 500 and 2000. It is found that the use of triple twisted tapes with smallest twist ratio of y/W =2.0 results in the highest heat transfer and friction factor while the use of the tapes with the largest twist ratio (y/W = 4.0) results in the highest thermal performance. The highest thermal performances based on the constant pumping power criterion of the tubes equipped triple twisted tapes with y/W = 2.0, 3.0 and 4.0 are 2.43, 2.63 and 2.73, respectively.
Keywords: Heat exchanger; Heat transfer enhancement; Swirl flow; Triple twisted tapes